The Effect of Product Quality, Electronic Word of Mouth and Promotion on Somethinc Skincare Purchase Decisions - Utami, Wahyu Putri; Handayani, Anita (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
The objective of this research is to analyze the partial and simultaneous effects of Product Quality, Electronic Word of Mouth (eWOM), and Promotion on the purchase decision for Somethinc products. The population in this study consists of all consumers who have used Somethinc products at least once in the Gresik region. The research employs primary data with a sample size of 160 respondents, using accidental sampling as the sampling technique. The analyses conducted include validity tests, reliability tests, normality tests, multicollinearity tests, heteroskedasticity tests, multiple linear regression, F-tests, t-tests, and coefficient of determination tests. The study concludes that Product Quality, Electronic Word of Mouth, and Promotion have a positive and significant partial effect on the purchase decision.